A rare arrhythmia in the newborn: posterior fascicular ventricular tachycardia - Yılmaz, Fatma Hilal; Oflaz, Mehmet Burhan; Tarakçı, Nuriye; Gültekin, Nazlı Dilay; Altunhan, Hüseyin (The European Research Journal, 2020)
Arrhythmias are most frequently seen in the neonatal period. Left posterior fascicular ventricular tachycardia is quite rarely seen in children and infants. In this case report, we present a newborn patient and management of left posterior fascicular ventricular tachycardia.